2011
DOI: 10.1126/scisignal.2001765
|View full text |Cite
|
Sign up to set email alerts
|

PreTCR and TCRγδ Signal Initiation in Thymocyte Progenitors Does Not Require Domains Implicated in Receptor Oligomerization

Abstract: Whether thymocytes adopt an αβ or a γδ T cell fate in the thymus is determined at a checkpoint (β-selection) by the relatively weak or strong signals that are delivered by either the pre-T cell receptor (preTCR) or the γδ TCR, respectively. However, how these signals are initiated, and how different signal strengths are generated, remains unclear. Although binding of thymic agonist ligand would predict strong signaling, the preTCR and TCRγδ appear to be capable of ligandindependent signaling. Some reports have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…Thymic ligand-independent signalling was similarly proposed for TCRgd, possibly mediated by oligomerisation of the variable region of TCRd [7]. However, a recent study has suggested that TCRgd complexes that lack variable domains, or that lack both variable and constant Ig-like domains, can still initiate signals that drive Recombination activating gene 2 (RAG-2)-deficient thymocytes toward a gd-like fate [6]. This implies that appropriate surface pairing of TCRg and TCRd chains that possibly bring CD3e-containing signalling modules into close proximity of available lymphocyte-specific protein tyrosine kinase (Lck) is sufficient for TCRgd signal initiation in DN thymocytes.…”
Section: Ligand-independent Tcrgd Signallingmentioning
confidence: 94%
See 2 more Smart Citations
“…Thymic ligand-independent signalling was similarly proposed for TCRgd, possibly mediated by oligomerisation of the variable region of TCRd [7]. However, a recent study has suggested that TCRgd complexes that lack variable domains, or that lack both variable and constant Ig-like domains, can still initiate signals that drive Recombination activating gene 2 (RAG-2)-deficient thymocytes toward a gd-like fate [6]. This implies that appropriate surface pairing of TCRg and TCRd chains that possibly bring CD3e-containing signalling modules into close proximity of available lymphocyte-specific protein tyrosine kinase (Lck) is sufficient for TCRgd signal initiation in DN thymocytes.…”
Section: Ligand-independent Tcrgd Signallingmentioning
confidence: 94%
“…This implies that appropriate surface pairing of TCRg and TCRd chains that possibly bring CD3e-containing signalling modules into close proximity of available lymphocyte-specific protein tyrosine kinase (Lck) is sufficient for TCRgd signal initiation in DN thymocytes. Thus, strong TCRgd signalling may not only be a consequence of ligand engagement; additionally, efficiently paired TCRg/TCRd chains that are expressed at the cell surface above a certain critical threshold will also commit DN progenitors to a gd cell fate [6].…”
Section: Ligand-independent Tcrgd Signallingmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-oligomerization of γδTCR at the cell surface of precursor thymocytes induces their differentiation into mature γδT cells (12,13). It has been proposed that γδTCR-ligand interaction determines the effector function of γδT cells (14).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, TCRgd can also mediate bselection-like differentiation to the DP stage. This is most evident in animals unable to express a functional pre-TCR, in TCRgd Tg mice in vivo (8,10,(19)(20)(21)(22)(23), and in cultures in which TCRgdexpressing progenitor cells are allowed to develop in vitro (24)(25)(26). Like b-selected DP cells, gd-selected DP cells silence TCRg gene expression and undergo TCRa rearrangements, indicating that they are bona fide ab-lineage cells (21).…”
mentioning
confidence: 99%